Beeswax rock art from Limmen National Park (Northern Territory), northern Australia: new insights into technique-based patterning and absence in the rock art record. Issue 2 (4th May 2019) - Brady, Liam M.; Bradley, John J.; Wesley, Daryl
Abstract: The known geographic distribution of beeswax rock art is largely restricted to the Arnhem Land plateau and Kimberley regions of northern Australia. While considerable research has focussed on the antiquity and meaning of beeswax rock art, much less attention has been directed to the nature and extent of the distribution pattern for this unique motif production technique. In this article, we present details of two beeswax motifs recently discovered in Marra Country at Limmen National Park (southwest Gulf of Carpentaria, Northern Territory). In the first instance, the motifs are explored in the context of their meaning, drawing on ethnography collected in the region over the last 40 years. The motifs are then used as a platform to engage with questions around the low frequency, and in some cases complete absence, of beeswax rock art across other areas of northern Australia. While it is highly unlikely there is one single, homogenous explanation for this in the Gulf country and northeastern Australia, we suggest that exploring the social, cultural and relational understandings of beeswax in these areas offers considerable potential to understand better how people engaged with and inscribed their cultural landscapes.